Quantificational strategies across language modalities - Quer, Josep (Proceedings of the Amsterdam Colloquium, 2011)
The study of quantification traditionally focused on structures where quantificational meanings are encoded in determiners. Only as a later development attention was paid to quantificational strategies that rely on adverbs, or af fixes. In this paper I discuss three varieties of quantificational strategies attested in two sign languages (ASL and LSC) and argue that even the apparent instances of determiner quantification in those languages make use of the more “constructional” way of encoding quantificational meanings that partially reflect the mapping onto tripartite structures overtly. Further, lexical quantification is addressed in the domain of distributivity.